Vulvar myoma: A case report and review of literature - Chi-Han Chang; Pei-Chen Li; Yung-Hsian Hsu; Dah-Ching Ding (Elsevier, 2021)
Objective: To present a case of vulvar myoma and the factors differentiating this tumor from Bartholin's cyst. Case report: A 50-year-old woman presented with a nodule over the left labia majora. Pelvic examination showed swelling and redness of the left labia majora. A 2-cm nodule with firm consistency was found near the vaginal opening. There was no inguinal lymphadenopathy. Bartholin's cyst was suggested, and oral cephalexin was prescribed for 1 week, but no improvement was seen. Therefore, she underwent excision of the nodule. Pathology revealed it to be a benign vulvar myoma. The patient recovered well, and no recurrence was noted after 2 months of follow-up. Conclusion: Vulvar myoma is rare. Sexual history, nodule consistency, and imaging are helpful, but the final diagnosis of vulvar myoma is usually made following surgical excision and histopathological analysis.